Cell Surface Expression and Function of the Macromolecular C1 Complex on the Surface of Human Monocytes - Hosszu, Kinga K.; Valentino, Alisa; Ji, Yan; Matkovic, Mara; Pednekar, Lina; Rehage, Nina; Tumma, Nithin; Peerschke, Ellinor I.; Ghebrehiwet, Berhane (Frontiers in Immunology, 2012)
The synthesis of the subunits of the C1 complex (C1q, C1s, C1r), and its regulator C1 inhibitor (C1-Inh) by human monocytes has been previously established. However, surface expression of these molecules by monocytes has not been shown. Using flow cytometry and antigen-capture ELISA, we show here for the first time that, in addition to C1q, PB monocytes and the monocyte-derived U937 cells express C1s and C1r, as well as Factor B and C1-Inh on their surface. C1s and C1r immunoprecipitated with C1q, suggesting that at least some of the C1q on these cells is part of the C1 complex. Furthermore, the C1 complex on U937 cells was able to trigger complement activation via the classical pathway. The presence of C1-Inh may ensure that an unwarranted autoactivation of the C1 complex does not take place. Since C1-Inh closely monitors the activation of the C1 complex in a sterile or infectious inflammatory environment, further elucidation of the role of C1 complex is crucial to dissect its function in monocyte, DC and T cell activities, and its implications in host defense and tolerance.